Perkembangan Kristologi Abad Pertama Sampai Dengan Abad Ke-5 - R, Rivaldo; Yustien, Yaer; Hawino, Andi Kristian Gagah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the development of Christological thought from the first to the fifth century AD using a qualitative-historical literature review method. Primary sources include ecumenical council documents (Nicaea 325 AD, Constantinople 381 AD, Ephesus 431 AD, Chalcedon 451 AD) and Church Fathers’ works, while secondary sources comprise related theological literature. Critical-historical and comparative analysis was employed to trace the evolution of Christological doctrine, including the Church’s responses to controversies such as Arianism, Nestorianism, and Monophysitism. The findings reveal that Christological understanding developed through theological dialectics influenced by internal factors (church authority, Scripture interpretation) and external factors (Greek philosophy, Roman politics). Ecumenical councils played a pivotal role in establishing orthodoxy, particularly the Council of Chalcedon (451 AD) which affirmed Christ’s two natures in one person. Key figures like Athanasius, Cyril of Alexandria, and Pope Leo I significantly contributed to maintaining this doctrinal balance. The study concludes that early Christian Christological developments not only formed the foundation of Christian faith but remain relevant to contemporary theological discourse.